2013
DOI: 10.1111/1754-9485.12024
|View full text |Cite
|
Sign up to set email alerts
|

Treatment response in the neck: p16+ versus p16− oropharyngeal cancer

Abstract: Nodal response rates following chemoradiotherapy appear to be similar in p16+ and p16- patients when assessed by either CA or PET/PET-CT. However, higher nodal CR was seen in PET/PET-CT compared with CA in both groups. Metabolic imaging is more accurate than CA in assessing nodal response post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 17 publications
0
30
0
4
Order By: Relevance
“…25,26 In another study, PET-CT was significantly more accurate than CT in identifying a complete nodal response, especially in patients with HPV-positive disease (93% vs. 50%). 21 A prospective singleinstitution study also showed that PET-CT surveillance was more cost-effective than CT surveillance, regardless of HPV status. 24 In the same study, CT followed by PET-CT in patients who did not have a response was shown to be only marginally more cost-effective than PET-CT alone, and with small changes in baseline assumptions and costs, CT followed by PET-CT ceased to be costeffective as compared with PET-CT alone.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…25,26 In another study, PET-CT was significantly more accurate than CT in identifying a complete nodal response, especially in patients with HPV-positive disease (93% vs. 50%). 21 A prospective singleinstitution study also showed that PET-CT surveillance was more cost-effective than CT surveillance, regardless of HPV status. 24 In the same study, CT followed by PET-CT in patients who did not have a response was shown to be only marginally more cost-effective than PET-CT alone, and with small changes in baseline assumptions and costs, CT followed by PET-CT ceased to be costeffective as compared with PET-CT alone.…”
Section: Discussionmentioning
confidence: 97%
“…Other researchers have reported that nodes with no FDG uptake have very high rates of regional control (93%), especially in HPV-positive disease. 21 We recommend that patients with an equivocal FDG uptake should continue to undergo neck dissection, especially if they have HPV-negative disease. However, patients with HPV-positive cancers who have enlarged nodes but no FDG uptake after chemoradiotherapy may be considered for close follow-up 11 with serial CT or PET-CT; this strategy may spare even more patients from undergoing a neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Post-treatment FDG PET-CT has an NPV up to 99% for nodal disease (when performed at 4 months), 17 benefit over conventional assessment (anatomical imaging and clinical examination) 18 and a high probability of long-term regional control (2.3% regional failure rate at 36 months). 19 A recent randomized controlled trial, the UK PET-NECK study, demonstrated that PET-CT surveillance had equivalent survival outcome at lower overall cost, when compared with routine neck dissection for N2/3 nodal disease post-CRT for advanced nodal disease.…”
Section: Current Uses Of Fdg Positron Emission Tomography-ct In Treatmentioning
confidence: 99%
“…Recent reports suggest human papillomavirus (HPV)þ nodal disease may take longer to reduce in size [11 & ], and therefore may present with equivocal FDG PET-CT scans (in particular with enlarged nodes on the CT scan component, but without FDG avidity) at the 12 week post-CRT assessment. Other recent reports suggest that patients who show no FDG uptake had very low recurrence rates, especially if they had HPVþ disease (93%) [9,12]. Therefore, patients with HPVþ disease who show enlarged nodes but no FDG uptake after CRT may be considered for close surveillance with serial frequent scans.…”
Section: Human Papillomavirus Disease and Equivocal Positron Emissionmentioning
confidence: 99%
“…Indeed, other studies that compared FDG PET-CT to CT have reported much higher efficacy of FDG PET-CT compared with CT in HPVþ patients. Mak et al [12] reported that FDG PET/PET-CT scanning at a mean time of 12 weeks (range 8-16 weeks) following treatment was significantly more accurate at predicting complete response (90%) compared with contrasted CT assessment (46%), and especially for HPVþ patients (93% vs. 50%). In one of the largest studies to date, which specifically considered FDG PET-CT response in HPVþ oropharyngeal cancer, FDG PET-CT at 12 weeks after CRT demonstrated high negative predictive value for loco-regional failure though with disappointing positive predictive value and sensitivity [15].…”
Section: Key Pointsmentioning
confidence: 99%